Berberine a traditional Chinese drug repurposing: Its actions in inflammation-associated ulcerative colitis and cancer therapy - Zhu, Cuipeng; Li, Kaiqi; Peng, Xiao-Xu; Yao, Tong-Jia; Wang, Zi-Yu; Hu, Ping; Cai, Demin; Liu, Hao-Yu (Frontiers in Immunology, 2022)
Berberine (BBR), an isoquinoline alkaloid extracted from Coptidis Rhizoma, has a long history to be used to treat dysentery in the clinic. Over the past two decades, the polytrophic, pharmacological, and biochemical properties of BBR have been intensively studied. When the pivotal functions of BBR including anti-inflammation, anti-bacterial, anti-oxidant, anti-obesity, and even anti-tumor have been discovered. However, the underlying mechanisms of BBR-mediated regulation are still needed to be explored. Given that BBR is also a natural nutrition supplement, the modulatory effects of BBR on nutritional immune responses have attracted more attention from investigators. In this mini-review, we summarized the latest achievements of BBR on inflammation, gut microbes, macrophage polarization, and immune responses associated with the potential mechanisms behind them in the pathogenesis and therapy of ulcerative colitis and cancer in recent 5 years. We also discuss the therapeutic efficacy and anti-inflammatory actions of BBR to benefit future clinical applications.